Installation and Training on the Automatic Weather Station Data Tool (ADT) for MALI-METEO - Faniriantsoa, Rija; List, Geneva (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
The recent expansion of weather observation networks has focused on the use of automatic weather stations (AWS). AWS offer a number of advantages, including automated reporting at very fine temporal resolution. The challenge that many national meteorological services have faced with the exploitation of AWS data is that initiatives and donors have provided different types of AWS from different suppliers, leading to a variety of systems and networks in multiple formats. Although applications are provided with each AWS network to access and visualize the data, data access is still done manually and station by station.